Corpos violados: crimes de defloramento na cidade de São Paulo, 1900 - 1932 - Nascimento, Débora Souza do (2019)
The purpose of this research was to recover the History of the Defloration Crime in Brazil between 1900 and 1932. This crime was legitimized by the Penal Code, Civil Code, by scientific knowledge of Forensic Medicine, and by the morals and good customs of that time. Thus, the female virginity was a medical, legal, physical and social issue. At that time, the Penal Code sustained that only “honest” women were deserving of justice and police protection. Therefore, although the women were victims of a crime, it was their conduct that was investigated and their bodies that were scrutinized at the Legal Medicine Chambers, because that society believed that “bad conduct” and “honesty” could be identified in the anatomy of the human body, in the female genital tract. The sources for this research were Forensic Examination Reports and some Police Surveys